2013
DOI: 10.14411/eje.2013.070
|View full text |Cite
|
Sign up to set email alerts
|

Ovaries of Puto superbus and Ceroputo pilosellae (Hemiptera: Coccoidea): Morphology, ultrastructure, phylogenetic and taxonomic implications

Abstract: Abstract. Ovaries of Puto superbus and Ceroputo pilosellae are composed of numerous short telotrophic ovarioles that are arranged around the distal part of the lateral oviduct. An individual ovariole consists of a distal trophic chamber (= tropharium) and proximal vitellarium. The tropharia enclose individual trophocytes (= nurse cells) and early previtellogenic oocytes termed arrested oocytes. A single oocyte develops in each vitellarium. Analysis of serial sections has shown that ovarioles of P. superbus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
2
8
1
Order By: Relevance
“…It should be stressed that results of studies of the symbionts of the genus Puto (Szklarzewicz et al 2010 ; Gruwell et al 2014 ; this study), as well as results of previous studies on the organization of their ovaries (for further details, see Michalik et al 2013 ), strongly support the current systematic position of these scale insects, i.e., in the separate Putoidae family within the archaeococcoid subgroup. This view is substantiated by the observation that the symbiotic bacterium Tremblaya phenacola in mealybugs from the family Pseudococcidae (subfamily Phenacoccinae), to which P. superbus was formerly classified (see “Introduction”), belongs to distinct group of bacteria, namely to the class Betaproteobacteria (Gruwell et al 2010 ; Koga et al 2013 ).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It should be stressed that results of studies of the symbionts of the genus Puto (Szklarzewicz et al 2010 ; Gruwell et al 2014 ; this study), as well as results of previous studies on the organization of their ovaries (for further details, see Michalik et al 2013 ), strongly support the current systematic position of these scale insects, i.e., in the separate Putoidae family within the archaeococcoid subgroup. This view is substantiated by the observation that the symbiotic bacterium Tremblaya phenacola in mealybugs from the family Pseudococcidae (subfamily Phenacoccinae), to which P. superbus was formerly classified (see “Introduction”), belongs to distinct group of bacteria, namely to the class Betaproteobacteria (Gruwell et al 2010 ; Koga et al 2013 ).…”
Section: Discussionsupporting
confidence: 82%
“…This means that the bacterium may feminize male embryos, kill male embryos, cause cytoplasmic incompatibility in infected males and uninfected females, and may also induce parthenogenesis (for further details, see Werren 1997 ; Stouthamer et al 1999 ; Werren et al 2008 ). The function of the bacterium in P. superbus remains unclear; however, both previous studies on ovaries (Michalik et al 2013 ) as present studies on symbionts did not reveal the negative influence of these bacteria on the reproduction of the host insect. As we have analyzed only two populations of P. superbus , it still remains unknown whether this bacterium is present in specimens from other locations.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…All germ cells residing in the ovariole (trophocytes, arrested oocytes, and developing oocytes) form one cluster of interconnected cells. Results of numerous studies from recent 30 years have shown that ovaries of scale insects markedly differ from those of the remaining hemipterans (Koteja et al, ; Książkiewicz, ; Michalik et al, ; Niżnik and Szklarzewicz, ; Ramirez‐Cruz et al, ; Szklarzewicz and Biliński, ; Szklarzewicz, , b, c; Szklarzewicz et al, ). First, the ovaries of scale insects are as a rule composed of an enormous number of ovarioles (e.g., 300 in Porphyrophora polonica ) that radially extend from the lateral oviduct.…”
Section: Introductionmentioning
confidence: 99%